2001
DOI: 10.1002/ar.1102
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular architecture of the rat choroid: Corrosion cast study

Abstract: This study presents the details of the microvasculature of the rat choroid visualized by scanning electron microscopy of vascular corrosion casts. Wistar Kyoto rats were anesthetized with intraperitoneal sodium pentobarbital. The vascular system was perfused with heparinized saline, and Mercox resin was injected into the cannulated carotid arteries. After polymerization of the resin, the vascular casts were macerated with potassium hydroxide, washed with water, and freeze dried. The casts were examined with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 27 publications
3
30
0
Order By: Relevance
“…2(f) and 3(f) are caused by major choroidal vessels. 22,23 To demonstrate further the complementary nature of these three modalities, a PAOM B-scan, 1D FA-SLO profile, and SD-OCT B-scan are compared in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…2(f) and 3(f) are caused by major choroidal vessels. 22,23 To demonstrate further the complementary nature of these three modalities, a PAOM B-scan, 1D FA-SLO profile, and SD-OCT B-scan are compared in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…The present study showed that although tropicamide had no significant effect on ChT, Eye cyclopentolate caused significant rapid choroidal thickening in healthy adults. Although the choroid is structurally constituted by the branches of ciliary arteries, 13 it also includes non-vascular smooth muscle cells, and a network of spindle-shaped or star-shaped cells. 1,14 These cells are considered to have a role in changing the ChT in proportion to the effects of local mediators and sympathetic and parasympathetic systems.…”
Section: Discussionmentioning
confidence: 99%
“…The iris, the cilia and the entire choroid of the rabbit are drained only by the vortex veins. In contrast, the rat eye has two drainage pathways; the posterior choroid is drained by the posterior ciliary vein, and the anterior segment of the eyeball is drained by the vortex veins [2,13]. Rats have been used exclusively in the past in order to study the elevation in intraocular pressure triggered by the cauterization of vortex veins.…”
Section: Discussionmentioning
confidence: 99%
“…The general distribution of the major vessels in the rabbit eyeball has already been outlined [5,11,12,20]. Scanning electron microscopy (SEM) has been used to study corrosion casts, and comparative descriptions of the rabbit's ocular vasculature have been published [2,5,8,11,12]. These studies indicated marked interspecies variation in vasculature among mammalian eyes.…”
mentioning
confidence: 99%